Archetype and time, place Language in architecture - Alshaikh, Ramzi; said, Nassiba; Abrahim, Tania Ahmed (Latakia University Journal -Engineering Sciences Series, 2019)
فقدت العمارة الحديثة وفي أغلب حالاتها شيئاً من هويتها حيث تلاشت الخصوصية والذاتية وذابت ملامح ومظاهر القيم المعمارية الخاصة بكل مكان وزمان، مما أدى للبحث في التاريخ لإيجاد الطابع كنوع من الحلول وذلك بالاعتماد على أحدث النظريات في العالم والتي تبحث في علم الظواهر في العمارة ، وذلك من خلال استثمار طاقات النماذج والأشكال الأصلية وترجمتها ودمجها مع مستجدات الحاضر ووسائله ، وبالتالي يمكن انتاج عمارة تجمع بين مبادئ العمارة الحديثة وتقنياتها وبين البنية التاريخية للأشكال المعمارية لتحقيق عمارة تواصلية تعبر عن فكر الانسان وماضيه وحاضره ومستقبله . يناقش البحث الحالي مفهوم النموذج وتطوره عبر الحقب التاريخية من خلال استعراض نتائج دراسات وطروحات منظرّي كل حقبة من هذه الحقب، وبشكل خاص في نظرية Schulz الباحث الذي تعمّق في مفهوم النموذج الأصلي وربطه بعلم الظواهر، والنظريات التي اعتمدها، ثم تحديد الخصائص التي يتحدد على أساسها النموذج الأصلي يليها خطوات ترجمته للوصول إلى النموذج المماثل. The Modern architecture lost something of its identity whereas most of privacy and self-vanished an architecture features, manifestation and values of each time and place; which led to research in history to find a character as a kind of solution by depending on the latest theories in the world which discussing the science of phenomena in architecture through investment potential types and original shapes, translated and merged it with the development of the present and its means, that can produce an architecture and its technology and between the historical infrastructure architectural forms to achieve a communication architecture that express human thought, his past, present and future. This current search discusses the concept of types and its evolution through historical periods through review of studies results and theorist's proposals of each era, and studies Schulz's theory the researcher who deepened the concept of archetype, and linking it with the knowledge of phenomena as well as the theories that he adopted, then select the properties that the archetype is determine on this basis follows by the steps to translate it to reach to the similar type.